Green Parties, Green Future From Local Groups to the International Stage - Gahrton, Per (Pluto Press, 2015)
Over the past four decades the world has seen a 'green awakening'. Green parties have been elected to parliaments and councils all over the world. A common set of environmental priorities have been promoted by green internationalisation and these parties are playing an increasing role at all levels of political decision-making. Will this awakening continue or will the greens be corrupted by power? What impact has their politics had? Will green thinking be able to compete with other ideologies in coping with the problems of the 21st century? Green Parties, Green Future analyses over a hundred of these parties' experience from all over the world. It reveals the story of the expansion and development of the movement, from local environmental groups to national and global decision-makers.